Lope De Vega. Carlos V en Francia. Edited from the Autograph Manuscript with Introduction and Notes by Arnold G. Reichenberger. - Valderrama Andrade, Carlos (Thesavrvs, 2023)
Bella edición de la "Comedia famosa de Lope de Vega Carpió dedicada a Gabriel Díaz, maestro de capilla insigne, en el Real Monasterio de la Encarnación".